Intruder traits modulate aggressive behavior of territory owners - Miyai, Caio Akira [UNESP]; Sanches, Fábio Henrique Carretero [UNESP]; Costa, Tânia Márcia [UNESP]; Barreto, Rodrigo Egydio [UNESP] (Springer Nature, 2020)
The prior residence effect consists of a higher probability of territory owners to win a fight against intruders, as observed in several territorial species across animal kingdom. However, in investigations on territorial behavior, intruder traits have been assumed as fixed. Thus, we used a territorial species as experimental model to evaluate the effect of intruder traits on aggressive behavior of territory owners. During fights staged between territory owners and intruders, intruder traits, linked with visual signals of social status (dominant-subordinate position), modulate fighting behavior of territory owners, but prior residence effect still occurred. Intruder traits must be addressed more effectively for improving the theoretical understanding of territoriality.